Deformasi Gunung Kelud Pascapembentukan Kubah Lava November 2007 - Haerani, Nia; Hendrasto, M.; Abidin, H. Z. (Indonesian Journal on Geoscience, 2010)
DOI:Â 10.17014/ijog.v5i1.90The eruption of Kelud Volcano in 2007 was started with an increase in the seismic activity on September 2007. It was ended with a lava dome formation inside the crater lake on 3 November 2007. This phenomenon showed the change of eruption behavior compared to the last eruption on February 1990 that was an explosive one. Result from the GPS observation method during three periods, which are: April, August, and October 2008 showed that the vector displacement on each measured point was affected dominantly by structural geology forces as a crustal stabilisation after the last phase of November 2007 eruption. There was also a minor displacement as the result of magma migration around the points that were close to the lava dome. The magma migration occurred in a relatively shallow depth and was associated with an aseismic zone. The deformation that occurred as a result of magma migration toward the surface was calculated to determine the magma supply and magma injected. The result then was compared to illustrate a mechanism of deformation during April â€“ October 2008. The comparison of magma supply and magma injected within these periods showed that the inflation still occurred, but it was not supported by a surface manifestation. This inflation could be false because of data discontinuity, or it is actually a part of deflation trend.